Combination of enucleation and partial nephrectomy techniques for robotic complex renal mass management in Smith-Magenis syndrome - Mikolaj Filon; Alejandro Sanchez; Bogdana Schmidt (Urology Video Journal, 2024)
Introduction: Smith-Magenis syndrome (SMS) is a rare genetic syndrome characterized by characteristic phenotypic features, developmental delay, cognitive impairment, and behavioral abnormalities. The diagnosis of SMS is established with suggestive clinical findings and either a heterozygous deletion at chromosome 17p11.2 that includes RAI1 or a heterozygous intragenic RAI1 variant. Individuals with a 17p11.2 deletion that includes FLCN may require management of features of Birt-Hogg-Dubé syndrome (BHD). The risk of cancer appears to be no greater than in the general population for most individuals with SMS. To date, renal tumors have been reported in three adults with heterozygous deletion of 17p11.2. Patient and Surgical Procedure: A 25-year-old male patient has a history of SMS, presented with back pain, and underwent abdominal ultrasound, which noted bilateral renal masses. A subsequent MRI was performed, noting 7 masses in the right kidney and 3 masses in the left kidney. He underwent renal biopsy of 3 masses on the right and 1 on the left, which were interpreted as renal hybrid oncocytic/chromophobe tumors (HOCTs). Germline genetic testing confirmed the patient carries an FLCN mutation. Haploinsufficiency of FLCN causes Birt-Hogg-Dubé (BHD), a syndrome characterized by pulmonary cysts, renal, and skin tumors. Of note, our patient only exhibits renal findings, with no characteristic skin lesions or pulmonary manifestations. Results: The operative time was 3 h with blood loss of less than 600 mLs. There were several off-clamp enucleations, followed by clamping of the renal hilum for 29 min, with resection of joint upper pole cystic masses in a traditional partial nephrectomy fashion, and enucleation of a deep hilar mass. This was followed by renorrhaphy and unclamping of the hilum. Additional small tumors were enucleated off-clamp. The patient was discharged uneventfully on post-operative day-1 (POD-1). The final pathology was notable for 6 hybrid oncocytic tumors, with the largest tumor measuring 6.6 cm (pT1b). There were no reported complications. Conclusion: In this report, we describe purely renal manifestations of a patient with Smith-Magenis syndrome with an FLCN mutation, without other findings of BHD syndrome. Given that these patients experience the same life expectancy as others with cognitive delay, they should be approached with similar care and the objective of nephron-sparing techniques. We demonstrate the feasibility of approaching the patient with a combination of enucleation off-clamp and traditional partial nephrectomy for large complex multiple renal masses. The technique emphasizes maximum preservation of renal parenchyma while minimizing the necessity for future procedures in cases of tumor growth and recurrence.